Polyphosphate synthesis is essential for phosphate and ATP homeostasis during nutrient upshift - Maria L. White; Julien Mortier; Lova Granqvist; Deike J. Omnus; Max Louski; Nick Crang; Berent Aldikacti; Valérie Migeot; Peter Chien; Marc Hennequart; Régis Hallez; Kristina Jonas (Proceedings of the National Academy of Sciences, 2026)
Inorganic polyphosphate (polyP) is a ubiquitous molecule found across all domains of life. Although implicated in diverse cellular processes, including phosphate storage, stress responses, and pathogenicity, loss of polyP synthesis typically causes only mild growth defects. Here, we demonstrate an essential physiological role for polyP synthesis during recovery from phosphate starvation, when cells transition from phosphate-limited to phosphate-replete conditions. Using a comprehensive transposon sequencing approach in Caulobacter crescentus , we identify genes conferring a fitness advantage during starvation for carbon, nitrogen, or phosphate and during subsequent recovery. We find that ppk1 , encoding the polyphosphate kinase responsible for polyP synthesis, is specifically required for recovery from phosphate starvation but dispensable for entry into starvation, a result confirmed with a ppk1 deletion mutant. Mutations that reduce phosphate uptake via the phosphate-specific transport system suppress the requirement for ppk1 , indicating that polyP synthesis prevents toxic accumulation of intracellular inorganic phosphate (P i ) upon refeeding. Our findings further show that buffering intracellular P i through polyP synthesis is critical for maintaining ATP homeostasis. Together, these results define a central role for polyP synthesis in regulating intracellular phosphate balance and ATP homeostasis, thereby facilitating adaptation to fluctuating nutrient conditions.